2016
DOI: 10.1007/s13762-016-1021-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of varying nitrogen levels on lipid accumulation in Chlorella sp.

Abstract: Microalgal lipids can be enhanced through varying nitrogen (N) content, and limited supply of nitrogen source seems to be valuable approach for increased lipid accumulation in microalgae. In this study, Chlorella sp. IM-02 was observed under fluorescence microscope for increased number of lipid bodies under nitrogen scarcity. Fourier transform infrared spectroscopy was used to determine spectral changes due to varying lipid content under nitrogen-starved (N 0 , without sodium nitrate), nitrogen-limited (N 0.1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 34 publications
3
14
0
Order By: Relevance
“…In Scenedesmus dimorphorus, neutral lipid or triglycerides appeared as yellow dots, whereas polar lipid and chlorophyll stained in red colour cells by Nile Red staining under fluorescent microscope with excitation wavelength at 420 nm and emission at 580-nm. Similar finding have been reported by many workers for lipid staining by using Nile Red dye for intracellular lipid identification (Cooksey et al, 1987;Matsunaga et al, 2009;Elumalai et al, 2011;Abdo et al, 2014;Kirrolia, 2015;Kiran et al, 2016).…”
Section: Resultssupporting
confidence: 88%
“…In Scenedesmus dimorphorus, neutral lipid or triglycerides appeared as yellow dots, whereas polar lipid and chlorophyll stained in red colour cells by Nile Red staining under fluorescent microscope with excitation wavelength at 420 nm and emission at 580-nm. Similar finding have been reported by many workers for lipid staining by using Nile Red dye for intracellular lipid identification (Cooksey et al, 1987;Matsunaga et al, 2009;Elumalai et al, 2011;Abdo et al, 2014;Kirrolia, 2015;Kiran et al, 2016).…”
Section: Resultssupporting
confidence: 88%
“…It is well‐known that microalgae have a potential capacity to accumulate a large quantity of lipid content under nitrogen‐limiting conditions. The inhibition of carbon assimilation in the TCA cycle and the use of nascent carbon in lipid metabolism through Acetyl‐CoA can explain these findings . Duong et al assessed the dominance of unsaturated fatty acids in isolated species of S. dimorphus from freshwater.…”
Section: Discussionsupporting
confidence: 74%
“…The lowest content of Chl‐ a , Chl‐ b , and carotenoid was found, that is, 2.91 ± 0.17, 1.15 ± 0.27, and 0.82 ± 0.16 µg/ml, respectively, at the concentration of 0 mM/L, whereas the highest content of pigments were observed in the concentration of 17.6 mM/L which was Chl‐ a , 14.15 ± 0.07 µg/ml; Chl‐ b , 7.39 ± 0.35 µg/ml, and carotenoid, 4.36 ± 0.32 µg/ml. Similar findings were recorded in the literature, which showed the reduction in the biosynthesis of photosynthetic pigments such as chlorophylls a and b in nitrogen limitation conditions . Therefore, a reduction in the pigment content could be one of the primary factors for decreasing photosynthetic activity in microalgae upon a decrease in the nitrogen content of the growth medium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under N depletion conditions, Chlorella stores carbon as triglycerides and starch, causing massive lipid production in the cell 21 . Recently, it has been reported that protein production under these conditions depends upon the N level and the duration of treatment 22 . The study showed that protein productivity in N starvation media was more than 40% higher than that in N-sufficient media over 4 days of Chlorella culture.…”
Section: Introductionmentioning
confidence: 99%